World wars and the modern age (John Wiley & Sons, Inc., 2004)
Experience explosive changes in American history with the people who witnessed them!From 1870 to 1950, America experienced an unprecedented era of rapid change and growth. A host of remarkable inventions led the way in transforming this nation into a major world power, and yet the forces of change often caused tremendous upheaval in people's lives. Now, World Wars and the Modern Age provides a rare glimpse into the day-to-day experiences of Americans who lived through Prohibition, the Roaring Twenties, the Great Depression, and two world wars. You'll be there as the New York Times offices are filled with electric light for the first time. You'll watch as immigrants flock to America's colorful, fast-growing cities, hoping to start anew. You'll read a young soldier's account of going "over the top" during the grim trench warfare of World War I-and, barely twenty years later, an eyewitness account of the surprise Japanese attack on Pearl Harbor that plunged America into World War II.From the personal writings of Henry Ford on his Model T automobile to songs of the Depression, from FDR's Inaugural Address to a G.I.'s description of D-Day, World Wars and the Modern Age presents a wealth of period documents, including diaries, letters, articles, advertisements, speeches, and more, from both famous figures and ordinary citizens. Find out how all of these American voices together helped make this country what it is today.AMERICAN HERITAGEr is well known for its magazine on American history, as well as its many highly acclaimed books, including the American Heritager Illustrated History of the United States and the American Heritager Illustrated History of the Presidents.